STRUKTUR GENETIK POHON INDUK Calophyllum inophyllum DI TEGAKAN BENIH PROVENAN BERDASARKAN PENANDA SIMPLE SEQUENCES REPEATS - ILG Nurtjahjaningsih; Purnamila Sulistyawati; Anto Rimbawanto (Jurnal Pemuliaan Tanaman Hutan, 2019)
This study aimed to assess genetic structure of Calophyllum inophyllum using simple sequences repeats (SSR) markers to control genetic diversity at a provenance seed stand. Leaf samples were collected for DNA templates and 6 SSR primers were used. Genetic data of 280 trees were analyzed by FSTAT software, while PCoA was analyzed by GeneAlex. Results showed that number of allele (NA) per SSR primer between 3 and 4, the allelic richness (AR) ranged 2.805 to 4.000, the gene diversity (HE) ranged 0.018 to 0.631, coefficient inbreeding (FIS) of overall SSR primers were insignificant deviate from Hardy-Weinberg Equilibrium, excepted NY3. The mean HE values in the TBP was in low (mean HE= 0.272). However, the mean coefficient inbreeding values was not significant. PCoA analysis showed that the seed stand consisted genetically related trees; the 280 trees originated from only 5-6 mother trees. This is because the stand was originated from a conservation stand with narrow genetic differentiation. Management of the seed stand was discussed.